2021
DOI: 10.1093/labmed/lmaa119
|View full text |Cite
|
Sign up to set email alerts
|

Smudge Cells in Chronic Lymphocytic Leukemia: Pathophysiology, Laboratory Considerations, and Clinical Significance

Abstract: Chronic lymphocytic leukemia (CLL) is the most commonly encountered leukemia in the clinical laboratory. Cytoskeletal defects in CLL lymphocytes can result in the formation of up to 75% smudge cells (SCs) during blood film preparation. Failure to account for these damaged lymphocytes in the white blood cell (WBC) differential diminishes the accuracy and reproducibility of the results. Lacking clear practice standards on handling SCs in CLL, different laboratories may employ different methods to mitigate SC-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The International Council for Standardization in Hematology (ICSH) recommends a solution for preparing and classifying smudge cells in peripheral blood after processing with one part of albumin and four parts of peripheral blood ( 25 ). Adding BSA to ethylenediaminetetraacetic acid (EDTA) acid-anticoagulated blood specimens for blood smears reduces the number of smudge cells and improves the consistency of morphological evaluation of peripheral blood smears in patients with chronic lymphocytic leukemia (CLL) patients ( 26 , 27 ). In a routine blood sample from a patient with CLL, 82 smudge cells were observed when 100 white blood cells were counted using CellaVision DI-60 software ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…The International Council for Standardization in Hematology (ICSH) recommends a solution for preparing and classifying smudge cells in peripheral blood after processing with one part of albumin and four parts of peripheral blood ( 25 ). Adding BSA to ethylenediaminetetraacetic acid (EDTA) acid-anticoagulated blood specimens for blood smears reduces the number of smudge cells and improves the consistency of morphological evaluation of peripheral blood smears in patients with chronic lymphocytic leukemia (CLL) patients ( 26 , 27 ). In a routine blood sample from a patient with CLL, 82 smudge cells were observed when 100 white blood cells were counted using CellaVision DI-60 software ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…More precise estimates of tumor burden would include absolute lymphocyte count (ALC) and number of B lymphocytes. Both ALC and WBC counts can suffer from inaccuracies due to the prevalence of smudge cells in CLL, often resulting in an underestimate of these counts [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…It contains cellular entities that have lost their structural integrity and cannot be morphologically classified any further. Classically, on the peripheral blood smear, the smudge cells have been thought to represent degenerated lymphocytes (DL), which are abundant in blood smears of patients with chronic lymphocytic leukemia (CLL) [ 22 ]. Such smudge cells are a result of breakdown of fragile leukemic lymphocytes and, therefore, represent an artifact of smear preparation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Classically, on the peripheral blood smear, the smudge cells have been thought to represent degenerated lymphocytes (DL), which are abundant in blood smears of patients with chronic lymphocytic leukemia (CLL) [ 22 ]. Such smudge cells are a result of breakdown of fragile leukemic lymphocytes and, therefore, represent an artifact of smear preparation [ 22 ]. We observed that a proportion of cell derived entities categorized as smudge cells by CellaVision ® morphologically resembled NETs.…”
Section: Introductionmentioning
confidence: 99%